2019
DOI: 10.1530/rep-18-0547
|View full text |Cite
|
Sign up to set email alerts
|

Cervical mucus sialic acid content determines the ability of frozen-thawed ram sperm to migrate through the cervix

Abstract: The aim of this study was to investigate the properties and to functionally characterize the cervical mucus that modulates sperm transport through the cervix by using ewe breeds with a divergent pregnancy rate (Belclare and Suffolk; high and low, respectively) following cervical insemination using frozen-thawed semen. Sperm number, as well as sialic acid and fucose content in both the channels and in the lumen of different regions of the cervix were quantified in inseminated Belclare and Suffolk ewes. Expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…2007 , 2019 ). In a recent study, we found fewer sperm in the cervical crypts of Suffolk ewes (low fertility) compared with Belclare ewes (high fertility), which was associated with higher sialic acid content in the cervix of Suffolk ewes compared with Belclare ewes ( Richardson et al. 2019 ).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…2007 , 2019 ). In a recent study, we found fewer sperm in the cervical crypts of Suffolk ewes (low fertility) compared with Belclare ewes (high fertility), which was associated with higher sialic acid content in the cervix of Suffolk ewes compared with Belclare ewes ( Richardson et al. 2019 ).…”
Section: Introductionmentioning
confidence: 76%
“…In the current study, sialyl-Tn antigen (Neu5Gcα2–6GalNAc, peak 18) was related to fertility, having lower abundance in Belclare ewes (medium fertility) than in Fur ewes (high fertility). However, Richardson et al. (2019 ) demonstrated increased amounts of Neu5Ac/Neu5Gc α2–6Gal- GalNAc in Suffolk ewes (low fertility) using a lectin assay.…”
Section: Discussionmentioning
confidence: 97%
“…An investigation into the rheology of the mucus between the breeds found that Suffolk ewes tended to have higher elastic and complex moduli than that from Belclare ewes leading to greater mucus penetration, as assessed in vitro (Richardson et al 2011). Glycosylation of cervical mucins also varied between breeds, with low fertility breeds (Suffolk) containing a significantly higher sialic acid content in the cervical channels than high fertility breeds (Belclare), while in vitro, the addition of sialic acid to spermatozoa increased mucus penetration (Richardson et al 2019). The immunoprotection of spermatozoa against immune recognition in the female uterus has been shown to be mediated by sialic acid (Alkhodair et al 2018), and therefore, differential glycosylation levels may mediate higher immunoreactivity and lower fertility in vivo.…”
Section: R8mentioning
confidence: 99%
“…It is not known if spermatozoa interact with these cilia in a similar manner to the ciliated epithelial cells in the oviduct. The presence of folds along the FRT suggests that they may have evolved to accommodate sperm transit as evidenced by the presence of spermatozoa deep within the cervical channels in cervices from ewes recovered shortly after insemination with F/T semen (Richardson et al 2019). The flow of mucus within these crypts and folds is thought to differ in composition and be slower than the stronger flow in the lumen of the cervix, which is critical for the protection of the upper FRT against the infiltration of pathogens (Cone 2009).…”
Section: Cervical Micro-anatomy and Its Role In Sperm Transportmentioning
confidence: 99%
“…Richardson et al. [ 17 ] reported that glycosylation of cervical mucins differs between Suffolk (low fertility) and Belclare (medium fertility), with higher sialic acid content in the cervical channels (where sperm progression occurs) of Suffolk compared with Belclare. In addition, there was higher expression of the sialyltransferase ST6GAL1 in the cervical channels of Suffolk compared with Belclare ewes, which supports the evidence of the role of the sialic acid in the inhibition of sperm transit through the cervix.…”
Section: Introductionmentioning
confidence: 99%